Correctional Officers' Mental Health Literacy and Attitudes Toward Offenders with Mental Illness - Hebert, Amber Rebecca (2020)
Overrepresentation of people with mental illness in the criminal justice system is a major societal problem. According to the Bureau of Justice Statistics, nearly three quarters of people housed in local jails report having symptoms suggestive of mental illness. Individual consequences to incarceration for people diagnosed with a mental illness include disruption in treatment, increase in symptomology, exposure to violence, and victimization. Correctional officers are an important component to the criminal justice system but their role in the lives of offenders with mental illness has been understudied. The current study explored the mental health knowledge, attitudes, and personal experiences of Louisiana jail correctional officers. Cross-sectional data was collected in a self-report survey from June 2019 until August 2019. The sample consisted of jail correctional officers (n=214) from 11 parishes in Louisiana. The average age of the sample was 36.1 years. A majority of the sample were male (69%), Caucasian (76.5%), and had a high school diploma (48.7%). The mean number of months as a correctional officer was 81.2. The multiple regression analysis tested the hypotheses that (H1) work experience, (H2) educational attainment, and (H3) contact with persons with mental illness predicted attitudes toward offenders with mental illness; (H4) mental health literacy predicted the level of negatively held stereotypes of mentally ill offenders; and (H5) that attending CIT training is predictive of mental health literacy. Work experience in months (H1) and contact with people with mental illness (H3) were not found to be predictors of attitude toward offenders with mental illness. However, educational attainment (H2) was found to be a significant predictor of attitude. Mental health literacy was found to be a predictor of negative stereotypical views of offenders with mental illness. Attending CIT training (H5) was not a predictor of mental health literacy. Further research is needed to determine if improved attitudes toward offenders with mental illness translate to improved outcomes for offenders with mental illness